Policy of Increasing Value-Added Tax from The Perspective of Maslahah Mursalah (Analysis of Act. No 7 Of 2021 Concerning Harmonization of Tax Regulations) - Jamilah Rizka; Muhammad Ramadhan (Journal Equity of Law and Governance, 2024)
Tax regulations in Indonesia have undergone many changes. The main factors are the global economy, basic needs of the country, development needs, and others. So it requires the community to work together to build the country through taxes. This research aims to find out the legal basis of the VAT increase policy, then find out the impact of the increase policy. And then how is the VAT increase policy if reviewed from the perspective of maslahah mursalah. In this study, the author uses normative research methods, with the Conceptual Approach and Statutes Approach. This research is descriptive analytical, data is collected through document studies, literature studies, and then analyzed using deductive thinking logic. The results of this study show that the increase in VAT rates is based on Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law). From the perspective of maslahah mursalah, which focuses on the benefit or public interest, this policy can be seen as an effort to achieve the welfare of the community at large. The increase in VAT has the potential to bring significant benefits by increasing the state budget that can be allocated for infrastructure, education, health, and other social programs, in line with the principle of public benefit. However, negative impacts such as inflation and a decrease in people's purchasing power, especially for low-income groups, need to be anticipated.